The Correlation Between Family Support and Adherence Level in Wound Care of Diabetes Mellitus Patients at the Surgical Department of Dian Husada Hospital - Siti Muthoharoh; Rina Widiyawati; Henny Chrisya Monicha (Jurnal Midpro, 2026)
Diabetes mellitus is a group of metabolic diseases characterized by an increase in blood glucose levels due to abnormalities in insulin secretion. One of the complications of diabetes mellitus is diabetic ulcers, and adherence to wound care is crucial to accelerate healing. However, patients with diabetic ulcers often fail to adhere to treatment, highlighting the need for family support to boost patient motivation. The purpose of this study is to investigate the relationship between family support and adherence to wound care in patients with diabetic ulcers. The design in this study was a correlational analytic design with a cross-sectional approach. The population of this study consisted of all patients with diabetic ulcers undergoing wound care at the Surgical Clinic of Dian Husada Hospital Mojokerto. The study 48 respondents, who were selected using total sampling. The results showed that family support for wound care among diabetes mellitus patients at the Surgical Clinic of Dian Husada Hospital Mojokerto was categorized as moderately adherent and less adherent, with 20 and 21 respondents respectively, representing 41.7% and 43.8%. The hypothesis test cross-tabulation analysis with a significance value of < α = 0.05 indicated a significant relationship between family support and adherence among diabetes mellitus patients. In providing wound care at the Surgical Clinic of Dian Husada Hospital Mojokerto, it is recommended that nurses involve the patient's family during the wound care process and facilitate family members in providing support to their loved ones undergoing  treatment.  This  can  help  boost  patient  motivation  and adherence to treatment.